Identification of the acoustic emission source during a comparative study on diagnosis of a spur gearbox - Tan, Chee Keong; Mba, David (Elsevier Science B.V., Amsterdam., 2005)
Condition monitoring of gears with vibration analysis is well established whilst the application of acoustic emission (AE) to gear defect diagnosis and monitoring is still in its infancy. This paper details results of an experimental programme to ascertain and validate the applicability of AE to seeded gear defect identification. Furthermore, comparisons are made to vibration diagnosis. As a direct consequence of the experimental programme, the relationship between temperature, oil film thickness and AE activity were investigated. It is shown that similar to the lubricant film thickness between non-conforming surfaces under isothermal conditions, AE activity is not influenced by load. Limitations of applying AE to seeded defect identification are presented and it is concluded that the source of AE activity is attributed to asperity contact.
Keywords: Acoustic emission; Asperity contact; Condition monitoring; Gear defect diagnosis; Lubricant film thickness; Rolling friction; Sliding friction